187k views
4 votes
AYUDEEEEEEEEEEEEEENME EESS PARA HOY!!!!

AYUDEEEEEEEEEEEEEENME EESS PARA HOY!!!!-example-1
AYUDEEEEEEEEEEEEEENME EESS PARA HOY!!!!-example-1
AYUDEEEEEEEEEEEEEENME EESS PARA HOY!!!!-example-2
User Voonic
by
4.9k points

1 Answer

2 votes

Answer:

(x+3)(x-3) = x²-9

(a+4)(a-4) = a²-16

(2/3x²y+1/4)(2/3x²y-1/4) = ((4x^4)y²)/9-1/16

(2x²+3y³)(2x²-3y³) = 4x^4-9y^6

(b-2)(b-2)(b-2) = b³-6b²+12b-8

Explanation:

(x+3)(x-3) = x²-9

(a+4)(a-4) = a²-16

(2/3x²y+1/4)(2/3x²y-1/4) = ((4x^4)y²)/9-1/16

(2x²+3y³)(2x²-3y³) = 4x^4-9y^6

(b-2)(b-2)(b-2) = b³-6b²+12b-8

User Mrimsh
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.